The Impact of Using Artificial Intelligence in the Audit Process to Enhance the Transparency of Financial Reports and its Reflection on the Reputation of the External Auditor - Mohammed Shani, Murtadha; Al-Tameemi, Layth Ali Hammadi (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2021)
Purpose – The papers. This research aims to identify the concept of artificial intelligence, demonstrate the impact of artificial intelligence in improving the external auditor’s skills, and demonstrate the extent to which the external auditor can use artificial intelligence.                                Design/methodology/approach: A review of previous research was conducted to determine and discuss what these researchers have found and the results they have reached. Artificial intelligence and some of its applications were studied to demonstrate its impact on the reputation of the auditor.                                                                            Findings – The use of modern technologies in the audit process in a way that is reflected in the transparency of financial reports, because this development may affect the reputation of audit offices, as the use of artificial intelligence in major audit companies in auditing companies’ data that is automated electronically may replace the external auditor in a way that threatens the future of auditors.                                                           Originality/value: The value of the paper lies in that it studies the problems of using artificial intelligence in the audit process in a way that reflects transparency in financial reports. Explaining the impact on the auditor’s reputation, this paper provides a general overview of the lack of significance